Investigating the physiological responses of Pacific white shrimp Litopenaeus vannamei to acute cold-stress - Zhenlu Wang; Yuexin Qu; Xiaolei Zhuo; Junyi Li; Jixing Zou; Lanfen Fan (PeerJ, 2019)
Background Litopenaeus vannamei is one of the most important aquaculture shrimps in the world and low temperatures present a serious challenge to its survival, growth, and distribution. Methods To investigate their physiological responses during acute cold-stress, L. vannamei were treated under acute cooling conditions from 28 to 13 °C with a cooling rate of 2.5 °C/2 h and were maintained at 13 °C for 12 h. Plasma metabolite concentrations, histological changes, and relative gene expression related to the unfolded protein response (UPR) pathway and apoptosis in the hepatopancreas and the hemocytes of L. vannamei were investigated. Results The results revealed that the concentrations of triglycerides, total cholesterol, and total protein in plasma reached their peaks at 23 °C, and then decreased to their minimum values at 13 °C for 12 h. The activity of alkaline phosphatase in the plasma decreased to its lowest level while the activity of alanine aminotransferase increased to its highest level at 13 °C for 12 h. The hepatic tubules became necrotic and the basement membranes were ruptured at 13 °C for 12 h. The gene expression related to UPR and apoptosis in the hepatopancreas and hemocytes was significantly altered by the decrease in the temperature. Discussion The results revealed that acute cold-stress caused histological damage in the hepatopancreas of L. vannamei, reducing its immunity. The three UPR pathways were involved in the process of acute cold-stress and the response of activating transcription factor 6 to UPR may be faster and more directthan the IRE1 and PERK pathways.